The role of the university in protecting society from terrorism, extremism and violence (Journal of the College of Basic Education, 2026)
Extremism and violence represent negative social phenomena and are among the most controversial and widely discussed issues by intellectual elites. These phenomena stem from various political, social, economic, intellectual, and religious causes, brought about by the rapid and successive developments of the modern era. Many young people are unemployed and suffer from high poverty rates, making them easy targets for extremist ideologies. This highlights the role of universities—represented by faculty and students—in confronting and addressing the phenomenon of extremism and terrorism. The study reached several conclusions, most notably that universities play a crucial role in combating extremism by educating students to respect others and their ideas, and by raising awareness of the dangers of terrorism to society. Based on these findings, the study recommends reinforcing values, principles, and respect for traditions, customs, and laws among students. It also suggests incorporating academic courses that address the dangers of terrorism and seriously studying students' problems, especially those exhibiting extremist or deviant thinking.